Kolaborasi Pendidikan dalam Membangun Karakter Anak Hebat melalui Tujuh Kebiasaan Positif - Risna, Inten; Nur, Maulida; Fadilah, Shifa; Safitri, Nabila Anzalia; Silfiani, Silfiani; Simanjuntak, Olga Theresia; Septiani, Wanda Zahra; Jamaludin, Jamaludin; Firdaus, Ahmad Maulana; Sutiawati, Sutiawati (Universitas Pahlawan Tuanku Tambusai, 2025)
Strengthening character education in early childhood is one of the strategic steps in preparing a generation that is intelligent and has good character. This Community Service Activity was carried out with the aim of increasing the role of collaboration between teachers and parents in developing the character of great children through seven positive habits in early childhood. The implementation was carried out through socialization with a participatory approach to teachers and parents at PAUD Darunnajwa regarding the urgency and implementation of the seven positive habits of great children. The results showed an increase in teachers' and parents' understanding of the urgency of character education in early childhood and the implementation in integrating character values through the habituation of 7 (seven) positive habits of great children and the importance of positive habits both at home and at school. This Community Service Activity provides recommendations to teachers and schools to be able to maintain consistent and sustainable cooperation in the formation of children's character.